Use of Scalp Hair as a Biomarker to Determine Airborne Heavy Metal Concentrations for the Academic Laboratory Employees - Al-Easawi, Nada Abdulrahman F.; Mahdii, Beadaa Abdalqadir; Abdul Rahman, Hind Jabbar (Iraqi Journal of Science, 2024)
Academic chemical laboratories (ACL) are considered public places the employees come in contact with a variety of pollutants. The aim of the current study was to detect heavy metals levels in the indoor air of ACL in two universities in Baghdad city and assess their levels in the academic employees’ scalp hair as biomarkers. Air samples inside ACL were collected to detect Fe, Cd, Zn, Pb and Cu. Scalp hair samples were collected from 40 adult chemical laboratory employees aged 30-60 years, who worked 5 days/week for 6 hours a day. Personal information relating to employees such as age, duration of exposure, smoking habit and sex, was collected as a questionnaire. The results of this study concluded that academic laboratory employees were exposed to high levels of heavy metals which was proven through the use of scalp hair; old ages, prolonged working periods, smoking habit have significant effects in increasing the levels of heavy metals in scalp hair, while the employees’ gender variation did not have a significant effect.